Answer:
The factorized expression is (-5) × (t - 2.747) ×(t - 1.747)
Step-by-step explanation:
The given expression is -5·t² + 5·t + 24
To factorize the expression by completing the square method, we equate the expression to zero to get;
-5·t² + 5·t + 24 = 0
WE divide by -5 to get;
t² - t - 24/5 = 0
t² - t = 24/5
t² - t + 1/4 = 24/5 + 1/4
(t - 1/2)² = 5.05
t - 1/2 = ±√5.05
t = 1/2 + √5.05, 1/2 - √5.05
The factorized expression becomes;
(t - 1/2 + √5.05) and (t - 1/2 - √5.05)
Which gives;
(t - 2.747) ×(t - 1.747)
The factorized expression is (-5) × (t - 2.747) ×(t - 1.747).
X = 4 , y = -1
Explanation:
solve by elimination ie eliminate x or y from the equations by performing operations on them.
first label the equations , to follow the process.
x - y = 5 ----------------(1)
x+ y = 3 ----------------(2)
If (1) and (2) are added then y will be eliminated.
(1) + (2) gives : 2x = 8 → x = 4
now substitute this value of x into either of the 2 equations and solve for y.
let x = 4 in (1) : 4 - y = 5 → -y = 1 → y = -1
check in (1) : 4-(-1) = 4+1 = 5
check in(2) : 4 - 1 = 3
Answer:
13 cm
Step-by-step explanation:
78/6=13
Cross-multiply:
7 * 3 = 5 * x
Divide each side by 5 :
X = 7 * 3 / 5 = 4.2
$139.23 you take the 239+34.70 then take 10% off